1991
DOI: 10.1007/bf00229845
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of visual responses in foveal V1 neurons following bilateral foveal lesions in adult monkey

Abstract: Cells in the foveal representation of V1 cortex of adult primates became visually responsive after normal sensory input was removed. Immediately after fovea were lesioned bilaterally, a region was found where no cells' activity could be modulated by visual stimulation. Recordings made in that deafferented zone at greater than 2.5 months after lesions revealed that activity of over half of the cells could be modulated by visual stimuli presented to intact peripheral retina. Although response characteristics mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
130
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(141 citation statements)
references
References 21 publications
10
130
1
Order By: Relevance
“…These findings pose a significant problem for fMRI and electrophysiological studies of cortical responses to scotomas reporting ectopic responses from a population of neurons in the SPZ as evidence of reorganization without taking into account effects of short-term adaptation (28)(29)(30)(31)(32)(33). Here, we achieved the same results in the SPZ of the rod scotoma with short-term exposure to scotopic conditions.…”
Section: Voxels With Prfs Overlapping the Rod Scotoma Show An Ectopicsupporting
confidence: 60%
See 2 more Smart Citations
“…These findings pose a significant problem for fMRI and electrophysiological studies of cortical responses to scotomas reporting ectopic responses from a population of neurons in the SPZ as evidence of reorganization without taking into account effects of short-term adaptation (28)(29)(30)(31)(32)(33). Here, we achieved the same results in the SPZ of the rod scotoma with short-term exposure to scotopic conditions.…”
Section: Voxels With Prfs Overlapping the Rod Scotoma Show An Ectopicsupporting
confidence: 60%
“…Each of these measurements was independent of long-term plasticity, which has particularly important implications for the interpretation of studies of cortical reorganization. Although several electrophysiological and fMRI studies propose long-term cortical reorganization as the primary mechanism for silencing, ectopic shifts, and pRF scaling within the SPZ (29,(31)(32)(33)35), we have acquired a similar pRF-level measurement and shown that these responses can arise during short-term cortical adaptation in the representation of pRFs with some overlap with the SPZ.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Does MT retinotopically reorganize to represent more of the preserved inputs from V1? Neurons in primary visual cortex acquire new receptive fields after being deprived by retinal lesions Heinen and Skavenski, 1991;Gilbert and Wiesel, 1992) (for review, see Kaas et al, 2001). Similar reorganizations might be expected in MT, because individual axons of neurons in V1 branch and form multiple terminal arbors over considerable distances in MT (Rockland, 1989).…”
Section: Discussionmentioning
confidence: 88%
“…Long-term changes were observed in primary auditory cortex as a result of cochlear lesions (Rajan, Irvine, Wise & Heil, 1993), and immediate changes were demonstrated in the same area as a result of learning (Weinberger, Hopkins & Diamond, 1984 (Eysel, GonzalezAguilar & Mayer, 1980;Eysel, Gonzalez-Aguilar & Mayer, 1981). Considering this demonstration in the LGN and the changes observed in somatosensory and auditory cortices, it is not surprising that the adult visual cortex can also reorganize (Kaas, Krubitzer, Chino, Langston, Polley & Blair, 1990;Heinen & Skavenski, 1991;Gilbert & Wiesel, 1992;Schmid, Rosa & Calford, 1993). However, the changes in primary visual cortex (V1) are not simply a reflection of those occurring in the LGN, since extensive changes in receptive field position can be observed a few hours after retinal laser lesions (Gilbert & Wiesel, 1992;Schmid, Calford & Rosa, 1994).…”
mentioning
confidence: 98%